2014
DOI: 10.1063/1.4863344
|View full text |Cite|
|
Sign up to set email alerts
|

Quantum mechanical study of solvent effects in a prototype SN2 reaction in solution: Cl− attack on CH3Cl

Abstract: The nucleophilic attack of a chloride ion on methyl chloride is an important prototype S N 2 reaction in organic chemistry that is known to be sensitive to the effects of the surrounding solvent. Herein, we develop a highly accurate Specific Reaction Parameter (SRP) model based on the Austin Model 1 Hamiltonian for chlorine to study the effects of solvation into an aqueous environment on the reaction mechanism. To accomplish this task, we apply high-level quantum mechanical calculations to study the reaction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 69 publications
2
32
1
Order By: Relevance
“…For all QM/MM calculations reported here, we employ the recently developed Specific Reaction Parameterization (SRP) AM1 Hamiltonian for Cl − attack on CH 3 Cl that has been demonstrated to accurately model this reaction in both the gas phase and in solution. 40 All non-QXD atoms in QM/MM simulations and calculations performed will use the LJ parameters provided in Table I.…”
Section: B Specific Reaction Parameterization Hamiltonianmentioning
confidence: 99%
See 2 more Smart Citations
“…For all QM/MM calculations reported here, we employ the recently developed Specific Reaction Parameterization (SRP) AM1 Hamiltonian for Cl − attack on CH 3 Cl that has been demonstrated to accurately model this reaction in both the gas phase and in solution. 40 All non-QXD atoms in QM/MM simulations and calculations performed will use the LJ parameters provided in Table I.…”
Section: B Specific Reaction Parameterization Hamiltonianmentioning
confidence: 99%
“…Free energy profile simulations were performed in order to test the effects of the QXD model on the attack barrier of a chloride anion reacting with methylchloride. In previous studies, 40 the traditional LJ model was shown to accurately capture this reaction barrier while using the LJ Cl − parameters set. The QXD parameter set used for these simulations is the set used to recapitulate experimental solvation free energies outlined in Subsection IV C. Results of these simulations, and comparisons to the standard LJ model with both the LJ Cl − and LJ CH 3 Cl parameter sets, can be seen in Figure 4.…”
Section: Qxd and Lj Free Energy Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…With this in mind, we wanted to understand how well NDDO methods perform for the description of bulk water. As a first test, we focus on a popular NDDO method, PM6, and look at an important structural descriptor of water, the oxygen–oxygen pair distribution function (Fig. ).…”
Section: Introductionmentioning
confidence: 99%
“…4,6,[15][16][17][18][19][20][21][22] These phenomena are especially apparent when studying highly charged systems such as RNA 11 as shown in Figure 1. To model these effects, simulations can be performed that include a vast buffer of explicit solvent molecules; however, such approaches are often extremely computationally demanding.…”
Section: Introductionmentioning
confidence: 99%